2010
DOI: 10.1007/s11249-010-9593-5
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Polytetrafluoroethylene, Nano-Titanium Dioxide, and Nano-Silicon Dioxide as Additives in Mixed Oil-Based Titanium Complex Grease

Abstract: Eight titanium complex greases (i.e., benzoic acid/stearic acid and sebacic acid/stearic acid titanium complex greases, and greases containing PTFE, or nanotitanium dioxide, or nano-silicon dioxide) were synthesized using 3-L reaction vessel. Their physical characteristics were characterized and their tribological properties were evaluated by using a four-ball tester. Chemical compositions of the boundary films generated on worn surfaces were analyzed with the use of scanning electron microscope and X-ray phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 12 publications
(11 reference statements)
1
24
0
Order By: Relevance
“…In this regard, researchers are actively involved in the search for lubricants which could prove to be very effective in the reduction of tribological wear in a wide range of industrial applications. For instance, different types of inorganic powders, such as molybdenum disulfide [1,2], titanium dioxide [3], ferric oxide [4], silicon dioxide [5][6][7][8], calcium carbonate [9,10], zinc oxide [11], lanthanum hydroxide [12], graphene [13], etc. were used as solid additives for improvement in tribological properties of different types of lubricants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, researchers are actively involved in the search for lubricants which could prove to be very effective in the reduction of tribological wear in a wide range of industrial applications. For instance, different types of inorganic powders, such as molybdenum disulfide [1,2], titanium dioxide [3], ferric oxide [4], silicon dioxide [5][6][7][8], calcium carbonate [9,10], zinc oxide [11], lanthanum hydroxide [12], graphene [13], etc. were used as solid additives for improvement in tribological properties of different types of lubricants.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of this work stemmed from the findings of the researchers [5][6][7][8], who used SiO 2 particles as the solid additive in lubricants for improving their antiwear performance. Since RH is a silica rich material [14][15][16][17][18]; therefore, it is anticipated that it might prove to be effective and cheap additive for the formulation of grease of improved tribological properties.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum non-seizure load (1100 N) of sample #11 is equal to the results in [12] when nano-titanium dioxide and nano-silicon dioxide were used as additives. Therefore, by addition of 3.0 wt% CeO 2 nanoparticles and 2.0 wt% SIB, Ti-complex grease exhibited excellent the combination of extreme pressure and anti-wear properties, although the P D , WSD and μ performance are not the optimal values.…”
Section: The Optimum Concentration Of the Sib And Ceo 2 Nanoparticlesmentioning
confidence: 78%
“…Chen et al [10][11][12] also reported that the benzoic acid-based titanium grease exhibited preferable anti-wear properties and pleasurable load-carrying capacity. It was believed that the improvements were due to titanic chemical films forming on and protecting the rubbing surface of the steel ball.…”
Section: Introductionmentioning
confidence: 99%
“…Greases incorporating nanoparticle [2] or nanotubes [3] such as nano-crystalline silicone dioxide display and nanocrystalline titanium dioxide noteworthy decrease the wear and friction [4]. Potassium Tetraborate and Nano boric acid have also been used fruitfully as resistance tumbling additives in oil and greases [5].…”
Section: Introductionmentioning
confidence: 99%